Eficácia de protocolos preventivos para as doenças respiratórias dos bovinos confinados - Magalhães, Layane Queiroz (2017)
The Bovine Respiratory Diseases (BRD) affect the productivity by compromising the health and welfare of cattle. Thus, the aim of these studies were related to the use of prophylactics and methaphylatics protocols to reduce morbidity of DRB, in addition to the participation of risk factors in the occurrence of BRD. The studies were carried out in a commercial feedlot in the northwest of Minas Gerais. Lung lesions occurence, the participation of viral and bacterial agents in DRBwere evaluated, and verified the effect of risk factors, vaccine and methaphylatic protocols on mobidity of BRD, in uncastrated male bovine with a mean of 20 months of age. The methaphylatic protocols with oxitetracyclin and tildipirosin defined by BRD risk were efficient in relation tomorbidity of DRB and lung lesions. Cattle wichwere vaccinatedagainst BRD viral agents on the entering of feedlot had 2.5 folds more risk of developing BRD, when compared with group that received booster before entry feedlot. It was observed that vaccination at the time of entry of animals against Bovine herpes virus 1 (BoHV-1), Bovine viral diarrhea vírus (BVDV), Bovine respiratory syncytial vírus (BRSV), Bovine parainfluenza type 3 virus, Mannheimiahaemolytica and Pasteurellamultocida is efficient to reduce morbidity of BRD and also has a positive impact in performance of feedlot cattle. Hence, the knowledge of the risk factors, of the viral and bacterial agents allows proposing methods to prevent these diseases and still improve animal welfare and reduce economic losses.